# what is the answer to -2/3 + 1/2?

### 15 Answers

- oldschoolLv 71 month ago
This method always works. The common denominator is the product of the two (or more denominators), 3x2 = 6 in this case. -2/3 = -4/6 and 1/2 = 3/6

-4/6 + 3/6 = (-4+3)/6 = -1/6

- 1 month ago
Hi

Denair

(-2/3)=(-4/6)

(1/2)=(3/6)

(-4/6)+(3/6)= (-1/6)

hence, the final answer is (-1/6)

- How do you think about the answers? You can sign in to vote the answer.
- 1 month ago
Ok so to find out what -2/3+1/2 is first you need to get both fractions the same denominator. In this case it is 6 because the lowest common denominator of 3 and 2 is 6.

-2/3+1/2=?

-2/3*(2/2)= -4/6

1/2*(3/3)= 3/6

-4/6+3/6= -1/6

- PuzzlingLv 71 month ago
When adding or subtracting fractions, you want to get the same denominator. In this case, the lowest common denominator (for 3 and 2) would be 6.

Rewrite each fraction with a denominator of 6.

-2/3 * (2/2) = -4/6

1/2 * (3/3) = 3/6

So your revised expression is:

-4/6 + 3/6

Now that you have the same denominator, just add the numerators:

(-4 + 3) / 6

= -1/6

Answer:

-1/6

- muthu1092000Lv 51 month ago
- 2/3 + 1/2

= - 2/3(2) + 1/2 (3) (to make the bottom number equal)

= -4/6 + 3/6

= -1/6